Resisting Silence towards Women: A Descriptive Analysis of Silence Methods in Magdalene Article Essays - Derosa, Allestisan Citra; Irwansyah, Irwansyah (Bina Nusantara University, 2021)
The research provided a descriptive analysis of six articles published by Magdalene, an Indonesian publication that resonated with feminists, pluralists, and progressive voices, to identify the subtle tactics men used to silence women. The idea of neutrality in language endured a long-standing debate between scholars in the communication field. In the perspective of feminist thinkers, language served a function of sexual division, placing men in domination and women in oppression. Women were constrained by a social system governed and communicated through a language that did not represent their experience and perspective. Men’s language denied and negated women’s authenticity. Women were only authentic when their voice was narrated by the language unfamiliar to the scream of their anguish and struggles. The language was not only a medium of expression but also a method of silence. In order to resist oppression, one must be critical of the technique men use in silencing women. Using silence methods from Muted Group Theory provided by Cheris Kramare, the research finds that silence dominantly occurs in the form of violence. The overlap of silence methods is mostly followed by censorship towards women. In one case of sexual harassment towards a female university student, the educational institution is considered the embodiment of patriarchal social construction for coercing silence to victims and doubling its function as sources of knowledge and sexual harassment perpetrators. Lastly, another finding suggests that men who strongly associate with feminist traits and whose sexual identification is against the dominant masculine norm are also disempowered.